Pain Catastrophizing Thoughts Explain the Link Between Perceived Caregiver Responses and Pain Behaviors of Patients With Chronic Musculoskeletal Pain - Mohammadi, Somayyeh; Alinajimi, Fatemeh; Esmaeilian, Nasrin; Dehghani, Mohsen; Khatibi, Ali (Frontiers in Psychology, 2020)
Purpose Caregivers’ responses to pain behaviors of patients with chronic pain have an essential role in how patients perceive their pain condition. The current study investigated the mediating role of pain catastrophizing on the link between perceived caregiver responses and patient pain behaviors. Materials and Methods The sample of this cross-sectional study consisted of 200 patients with chronic pain (mean of age = 44.6; 71.5% were female). Participants responded to measures assessing their perception of their caregiver responses to their pain, their pain catastrophizing thoughts, and their pain behaviors. Results The mediation analyses showed that perceived distracting responses were negatively related to pain catastrophizing level in patients, which in turn was positively associated with expressing pain behaviors. Besides, perceived caregiver negative responses were positively associated with catastrophizing thoughts, which in turn was positively related to expressing pain behaviors. Conclusion Patients’ perceptions regarding how their caregiver responds to their pain condition can be related to their thoughts about their pain and how they react to their pain situation. Investigating the external sources that might have an impact on patients’ reactions to their pain, especially when those external sources are caregivers who, in most situations, are with the patients for a prolonged duration, is essential.